Cancer detection using image processing techniques based on cell counting, cell area measurement and clump detection - Pavel, Monirul Islam; Sadique, Ashique Mohammad; Ritul, Rifat Ahmed; Khan, Synthia; Nath, Snigdha (BRAC Univeristy, 2018)
Cataloged from PDF version of thesis report.